Vicinal, Double C-H Functionalization of Alcohols via an Imidate Radical-Polar Crossover Cascade - Prusinowski, Allen F. (J Am Chem Soc, 2020)
A double functionalization of vicinal sp(3) C-H bonds has been developed, wherein a β amine and γ iodide are incorporated onto an aliphatic alcohol in a single operation. This approach is enabled by an imidate radical chaperone, which selectively affords a transient β alkene that is amino-iodinated in situ. Overall, the radical-polar-crossover cascade entails the following key steps: (i) β C-H iodination via 1,5-hydrogen atom transfer (HAT), (ii) desaturation via I(2) complexation, and (iii) vicinal amino-iodination of an in situ generated allyl imidate. The synthetic utility of this double C-H functionalization is illustrated by conversion of aliphatic alcohols to a diverse collection of α,β,γ substituted products bearing heteroatoms on three adjacent carbons. The radical-polar crossover mechanism is supported by various experimental probes, including isotopic labeling, intermediate validation, and kinetic studies.